Analisis Pengaruh Tingkat Inflasi, Transaksi Pasar Uang Antar Bank Syariah (PUAS) dan Investasi Syariah terhadap Imbal Hasil Sertifikat Bank Indonesia Syariah (SBIS) - febi febi; Desi Nurmaida (IAIN Langsa, 2018)
This research aims to analyze the effect level of inflation, transaction of interbank sharia money market and sharia investment to yield sharia certificate of Bank Indonesia period January 2012 - December 2017. The data used are time series data period January 2012 - December 2017 published by BI and OJK. The method of analysis used in this research is Vector Auto Regression (VAR) models. Results of Granger Causality analysis show that, there is a pattern of one-way causality between inflation with transaction of interbank sharia money market (PUAS) and yield sharia certificate of Bank Indonesia (SBIS), there is a pattern of one-way causality between sharia investment with transaction of interbank sharia money market (PUAS) and there is not a pattern of one-way causality between yield sharia certificate of Bank Indonesia (SBIS) with transaction of interbank sharia money market (PUAS) and sharia investmentin Indonesia period 2012-2017. Results of Impulse Response Function analysis show that, inflation response most quickly reach stability when shock occur in the variable transaction of interbank sharia money market (PUAS). Transaction of interbank sharia money market (PUAS) response most quickly reach stability when shock occur in the variable sharia investment. Sharia investment response most quickly reach stability when shock occur in the variable sharia investment. Yield sharia certificate of Bank Indonesia (SBIS) response most quickly reach stability when shock occur in the variable transaction of interbank sharia money market (PUAS). Result of Variance Decomposition analysis show that, the variable that gives the most contribution to inflation, transaction of interbank sharia money market (PUAS), sharia investment and yield sharia certificate of Bank Indonesia (SBIS) is inflation, transaction of interbank sharia money market (PUAS), sharia investment and yield sharia certificate of Bank Indonesia (SBIS) it self.